Draft Genome Sequences of the Obligatory Marine Myxobacterial Strains Enhygromyxa salina SWB005 and SWB007 - Amiri Moghaddam, Jamshid (Genome Announc, 2018)
The two marine myxobacterial strains Enhygromyxa salina SWB005 and SWB007 were isolated from coastal soil samples using Escherichia coli as bait for these predatory strains. These strains produce unique specialized metabolites. Genomes were assembled into 312 contigs for E. salina SWB005 (9.0 Mbp) and 192 contigs for E. salina SWB007 (10.6 Mbp).